Evaluasi Usability pada Website Skilvul sebagai Massive Open Online Courses (MOOCS) menggunakan Metode Think-Aloud - Rachel Jessica Silalahi; Hanifah Muslimah Az-Zahra; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Skilvul is one of the MOOCs in Indonesia, providing digital skills learning content with the "blended-learning" method in online and offline form. Through initial observations, several Skilvul users expressed problems related to inputting answers to practice questions, some actions were not given alerts or pop-ups, and the fastest alternative action to exit the system. So the purpose of the research is to find problems, evaluate, analyze, and provide recommendations for improvement. The method used is Think-Aloud and analysis using Usability Checklist for MOOCs. A total of 8 users conducted online testing using 12 task scenarios and were given severity ratings related to the problems found. Severity ratings are the severity of the problem. There were 27 problems consisting of 9 problems found by only users and 18 problems found by researchers only. Recommendations for improvement are given starting with severity ratings with the highest score being 4 (catastrophe), moderate being 3 (major problem), to the lowest being 2 (minor problem) and for severity ratings 1 (cosmetic problem) no recommendation for improvement is given. Recommendations for improvement are given based on the usability checklist for MOOCs. There are 7 guidelines, namely general courses, courses based on material presentation, information and notifications, interaction and discussion, error prevention, other contexts, and general usability. Other recommendations are also given based on the similarity of problems obtained by users and analyzed whether they are feasible to be followed up.